2022
DOI: 10.3389/fmicb.2022.795777
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Analysis Reveals a Changing Microbiome Associated With the Depth of Invasion of Oral Squamous Cell Carcinoma

Abstract: The relationship between oral squamous cell carcinoma (OSCC) development and the microbiome has attracted increasing attention. The depth of invasion (DOI) is an important indicator of tumor progression, staging and prognosis, and the change in the oral microbiome based on the DOI is unclear. This report describes the use of metagenomic analyses to investigate the relationship between the oral microbiome and the DOI. Forty patients in different DOI categories were recruited; 10 healthy people served as the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 65 publications
3
21
0
Order By: Relevance
“…Thus, the best classification feature is found, and the prediction result is decided. Therefore, in this study, one thousand classification trees were constructed in the random forest algorithm and mixed 50 times, and the importance of the features was evaluated according to Previous studies indicate that SVM-RFE is a machine learning method based on the support vector machine (SVM), which removes the feature vectors generated by SVM, finds the best variables, and establishes a SVM model with the help of e1071 software package to further identify the above biomarkers for disease diagnosis [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the best classification feature is found, and the prediction result is decided. Therefore, in this study, one thousand classification trees were constructed in the random forest algorithm and mixed 50 times, and the importance of the features was evaluated according to Previous studies indicate that SVM-RFE is a machine learning method based on the support vector machine (SVM), which removes the feature vectors generated by SVM, finds the best variables, and establishes a SVM model with the help of e1071 software package to further identify the above biomarkers for disease diagnosis [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Enrichment of ASVs from the Fusobacterium genus in OSCC samples in our analysis was in line with the other findings, both within and outside the oral cavity. Fusobacterium nucleatum has been found to be an active bacterium in promoting oral cancer by several mechanisms (McIlvanna et al, 2021 ; Zhang S. et al, 2021 ; Liu et al, 2022 ). F. nucleatum has also been traditionally associated with chronic inflammation, the promotion of EMT among epithelial cells, the alteration of immune response in the oral cavity, and significant roles in several oral diseases including oral cancer and endodontic infections (Shao et al, 2021 ).…”
Section: Analysis Of Results and Discussionmentioning
confidence: 99%
“…The study demonstrated that abundances of F. nucleatum , Capnocytophaga sputigena , Porphyromonas endodontalis , and Gemella haemolysans were significantly increased in patients with oral squamous cell compared with the controls and that the abundances of P. endodontalis , Gemella morbillorum , and G. haemolysans increased with increasing depth of invasion of malignancy suggesting a dose-related relationship. In contrast, the abundances of P. melaninogenica , Haemophilus parainfluenzae , and Neisseria flavescens decreased with increasing depth of invasion suggesting a similar relationship [ 51 ]. A separate study that may provide prognostic value describes the abundance of Schlegelella and Methyloversatilis in HNSCC tumors as a marker of poor prognosis.…”
Section: The Microbiome Of Structures Of the Aerodigestive System Thr...mentioning
confidence: 99%